Suicidal ideation in Mexican chemical engineering students - García-Montalvo, Iván Antonio; Matías-López, Diana; Hernández-Bautista, Emilio; Chávez-Montaño, Aurora; García-Montalvo, Gildardo Oswaldo; López-Ramírez, Enrique; Sánchez-Medina, Marco Antonio (Frontiers in Education, 2025)
Mental health is a crucial component of overall wellbeing, as it significantly impacts the quality of life and interpersonal relationships. Suicide, one of the leading causes of death worldwide, particularly affects young people between 15 and 29 years of age. This phenomenon is linked to factors such as mental disorders, family problems, socioeconomic constraints, and substance abuse. In the university setting, students face emotional challenges stemming from academic stress, separation from the nuclear family, and social pressure. These factors increase their vulnerability to suicidal ideation. In careers such as Chemical Engineering, academic stress is exceptionally high due to the complexity of the studies; despite the above, it is not one of the professions with the highest rates of suicidal ideation, but its impact on the mental health of students requires attention. Mexican universities have implemented psychological support programs to address these problems. It is essential to continually evaluate these programs to enhance their effectiveness and respond effectively to student needs. Further research is needed on the specific factors affecting chemical engineering students to design more effective preventive strategies.